Time-motion and physiological profile of football training sessions performed by Under-15, Under-17, and Under 19 elite Portuguese players - Abade, E. A.; Gonçalves, B. V.; Leite, N. M.; Sampaio, J. E. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To provide the time-motion and physiological profile of regular training sessions (TS) performed during the competitive season by under-15 (U15), under-17 (U17), and under-19 (U19) elite-level Portuguese soccer players. Methods: One hundred fifty-one elite players of U15 (age 14.0 ± 0.2 y, n = 56), U17 (age 15.8 ± 0.4 y, n = 66), and U19 (age 17.8 ± 0.6 y, n = 29) participated in the study during a 9-wk period. Time-motion and body-impact data were collected using GPS technology (15 Hz) across 38 randomly selected TS that resulted in a total of 612 samples. In addition, heart rate (HR) was continuously monitored (1 Hz) in the selected TS. Results: The total distances covered (m) were higher in U17 (4648.3 ± 831.9), followed by U19 (4212.5 ± 935.4) and U15 (3964.5 ± 725.4) players (F = 45.84, P < .001). Total body impacts and relative impacts were lower in U15 (total: 490.8 ± 309.5, F = 7.3, P < .01), but no differences were identified between U17 (total: 584.0 ± 363.5) and U19 (total: 613.1 ± 329.4). U19 players had less high- and very-high-intensity activity (above 16 km/h; F = 11.8, P < .001) and moderate-intensity activity (10.0-15.9 km/h; F = 15.07, P < .001). HR values showed significant effects of zone (F = 575.7, P < .001) and interaction with age group (F = 9.7, P < .001), with pairwise differences between all zones (zone 1, <75%; zone 2, 75-84.9%; zone 3, 85-89.9%; zone 4, =90%). All players spent most of their time below 75% HRmax (U15, ~50%; U17, ~42%; U19, ~50%). Conclusion: Results showed high variability between TS, refraining from identifying meaningful trends when measuring performance, although different demands were identified according to age group. The U15 TS were less physiologically demanding, probably because of increased focus on small-sided games to develop basic tactical principles and technical skills. The focus on game-like situations imposed higher external and internal workloads on U17 and U19 players